2022
DOI: 10.3390/brainsci12020292
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination and Mental Disorders, What Has Been Accomplished and Future Direction

Abstract: The consequences of the pandemic on mental health are among the most important side effects of COVID-19. Wide concerns have emerged both regarding vaccine hesitation in the general population, and the vaccine’s implementation plan. The aim of this study is to evaluate how the scientific community has investigated the relationship between the COVID-19 vaccine and mental disorders. Contrary to expectations, having a full-blown psychiatric pathology seems to positively affect the attitude towards the vaccine, exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Diagnosis of PTSD and vaccine hesitancy levels are positively related in clinical practice [ 37 ], in contrast to clinical depression and anxiety levels [ 38 ]. However, the concept of fear of vaccination [ 39 , 40 ] has rarely been explored in comparison to vaccination hesitancy [ 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of PTSD and vaccine hesitancy levels are positively related in clinical practice [ 37 ], in contrast to clinical depression and anxiety levels [ 38 ]. However, the concept of fear of vaccination [ 39 , 40 ] has rarely been explored in comparison to vaccination hesitancy [ 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study in Turkey concerning patients with schizophrenia found that the use of available resources, to changes in daily living, and social interaction and support were facilitators in coping with the pandemic burden [63]. These observations are indirectly supported by a recent review regarding the concerns and fears of patients with mental disorders toward COVID-19 vaccination, which highlights that, contrary to expectations at the beginning of the pandemic, SMI may positively affect attitudes toward the vaccine [64]. This finding suggests that the ability to seek support, which may influence adherence, could represent a crucial protective personality trait in these patients.…”
Section: Discussionmentioning
confidence: 93%
“…Importantly, several countries have already prioritized vaccination for people with severe mental illness [ 169 , 170 ]. The relationship between COVID-19 vaccination and mental disorders was investigated in several studies [ 171 , 172 , 173 ].…”
Section: Covid-19 Vaccine and Mental Disordersmentioning
confidence: 99%